Competence’s Theorem: Solving Problems of Water Utilities - Tugushev, Marat S. (International Journal of Energy Economics and Policy, 2018)
This article as a whole introduces a competence’s theorem as scientific cybernetic ideology underlying the optimal regulation of the public services or utilities. In practical applicability, the article considers the most important water utilities, where two specified symptomatic paradigms (non-revenue water and service regulation modeling) that seem to be different have common problems related to the neglecting of the basics of public utilities regulation such as information theory, system theory and cybernetics. The competence’s theorem demonstrates that only a model of computing machine being isomorphic to legal State could be an optimal good regulator of the public utilities. Keywords: Competence’s theorem; solving problem; water utilities JEL Classifications: L95, Q25